Perancangan Sistem Informasi Penjualan Berbasis Web Pada Dina Boutique Palembang - Tri Wahyu Cahyo Septa; Triana Elizabeth (STMIK Banjarbaru, 2026)
Dina Boutique still conducted sales transactions manually through WhatsApp, resulting in unstructured data recording, delayed information, and discrepancies between sales and stock data. This study aimed to design an integrated web-based e-commerce sales information system using the Laravel framework connected to the stock management system. The Rapid Application Development method was applied through the stages of Requirements Planning, User Design, Construction, and Cutover. Data were collected through interviews, observations, and documentation, while system testing was conducted using Black Box Testing. The results showed that the developed system was able to support online sales transactions, automatically update stock data, provide real-time sales reports, and display sales analysis Dashboards. Based on the testing results, all main system functions operated according to user requirements and improved the operational efficiency of Dina Boutique.Keywords: Sales information system; E-commerce; Laravel; System integration; Sales Dashboard.AbstrakDina Boutique masih melakukan proses transaksi penjualan secara manual melalui WhatsApp sehingga menyebabkan pencatatan data kurang terstruktur, keterlambatan informasi, dan ketidaksesuaian antara data penjualan dengan stok barang. Penelitian ini bertujuan untuk merancang sistem informasi penjualan e-commerce terintegrasi berbasis web menggunakan framework Laravel yang terhubung dengan sistem manajemen stok. Metode Rapid Application Development digunakan melalui tahapan Requirements Planning, User Design, Construction, dan Cutover. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi, sedangkan pengujian sistem dilakukan menggunakan Black Box Testing. Hasil penelitian menunjukkan bahwa sistem yang dikembangkan mampu mendukung transaksi penjualan online, memperbarui stok secara otomatis, menyajikan laporan penjualan secara real-time, serta menyediakan Dashboard analisis penjualan. Berdasarkan hasil pengujian, seluruh fungsi utama sistem telah berjalan sesuai dengan kebutuhan pengguna dan membantu meningkatkan efisiensi operasional Dina Boutique.